IMPLEMENTASI ALGORITMA UNARY CODING UNTUK MENGKOMPRESI TEKS TERENKRIPSI EL GAMAL - Fitri Angelina Siahaan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
The speed at which information is transmitted is indispensable in current technological developments. Information is a message or a collection of messages or a data that has been processed so as to produce something needed by the party in need. Information can take the form of various data formats, including text, video or images. The problem of the speed of information delivery is often slightly inhibited due to the large file size of the information. In addition, the security factor is also very important, as many irresponsible parties will try to steal the information and may harm the stolen information when it is misused. The process undertaken in this study is to analyze the process of encryption and decryption algorithm El Gamal and compression algorithm Unary coding then designing security and compression applications using design tools such as Unified Modeling Language (UML) and Microsoft Visual Basic 2008 to simplify the making of applications. After completion of the design, then the file will be encrypted and compressed using applications that have been designed. Then, the result of the process is a text file that can not be understood and has a size smaller than the original.